Principals and Teachers’ Attitudes Towards Inclusion in Israel - Hess, Itay; Zamir, Sara (Journal of the American Academy of Special Education Professionals, 2016)
The main goal of this study was to determine whether, in schools that practice inclusion, there is a correlation between the attitudes of school principals and teachers in their schools, towards inclusion of student with special needs. For this purpose, 38 schools were sampled in each of which the school principal and five teachers who work with students from the school’s inclusion program–were to respond to questionnaires about their attitudes towards inclusion. A total of 38 school principals and 195 teachers participated in this study. In addition, the principals were asked to describe their management styles concerning the inclusion of students with special needs. The teachers also completed questionnaires about the school climate. The main findings indicated that principals’ positive attitudes towards inclusion were associated with teachers’ positive attitudes. In addition, a correlation was found between styles of management that support inclusion (such as support for changes to adapt the school for inclusion) and teachers’ perceptions of a positive school climate.